UMPSA establishes Rail Training Centre in collaboration with LZRVTC - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUANTAN, 11 December 2023 - The strategic collaboration between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Liuzhou Railway Vocational Technical College (LZRVTC) saw the establishment of a Rail Training Centre at the university to empower the field of rail engineering and technology that supports the National TVET Empowerment Agenda.